2020
DOI: 10.4081/aiua.2020.4.321
|View full text |Cite
|
Sign up to set email alerts
|

Complications of endourological procedures and their treatment

Abstract: Endourological treatment for urinary stones and other obstructive urinary tract diseases is minimally invasive but in some cases it involves serious complications. This collection of cases describes some complications of endourological procedures and how they were treated. Case 1: A case of right ultrasound-guided percutaneous nephrostomy found to be misplaced in the inferior vena cava. The case was safely managed, but it showed that ultrasound guidance alone may be insufficient so it is recommended that percu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Although majority of the encrusted ureteral stent need multimodal management, Lio et al (17) From our results, the average total number of procedures carried out was 3 ± 1.08 with a range of 2 to 5 per EUS removal and the average time of hospital stays was 2.69 ± 1.43 days with a range of 1 to 6 days per EUS removal. Alnadhari et al (4) in their study reported a mean of 2.25 urologic procedures needed per EUS removal with a range of 1 to10 procedures performed in a single or multiple anesthetic sessions.…”
Section: Challenges In the Management Of Encrusted Stentsmentioning
confidence: 58%
“…Although majority of the encrusted ureteral stent need multimodal management, Lio et al (17) From our results, the average total number of procedures carried out was 3 ± 1.08 with a range of 2 to 5 per EUS removal and the average time of hospital stays was 2.69 ± 1.43 days with a range of 1 to 6 days per EUS removal. Alnadhari et al (4) in their study reported a mean of 2.25 urologic procedures needed per EUS removal with a range of 1 to10 procedures performed in a single or multiple anesthetic sessions.…”
Section: Challenges In the Management Of Encrusted Stentsmentioning
confidence: 58%
“…However, some minor complications, such as haematuria, hydronephrosis, ureteral obstruction by stone fragments and ureteral double J stent dislocation, might be not significant in a patient with two functional kidneys but could be more important for patients with solitary kidneys requiring urgent intervention. Concern about the risk of renal dysfunction and subcapsular hematoma associated with the use of high-pressure irrigation during RIRS has been raised (13).…”
Section: Discussionmentioning
confidence: 99%